L’opération de parcours et l’expression de la durée : étude de for et de in. - Agnès Leroux (Corela)
In this article, written within the frame of the Theory of Enunciative Operations by Antoine Culioli, we aim at redefining the expression of duration through the enunciative operation of scanning.We first worked on and analysed a corpus of English utterances which we will extend to French utterances later on in order to eventually redefine the concept of duration and its relation to Time. The corpus is essentially made of real utterances containing temporal for or in with a temporal quantification in negative clauses, which were chosen from literature and magazines. We observed, analysed and organised this corpus into categories to show how the relation between the process of the verb and what is usually called the interval of time induces us to shed the linear traditionnal representation of time in language : the expression of duration could correspond to the scanning of a class of instants by the occurrence of a verb.